The Representation Of Religious Meaning In Perunggu’s “33x”: A Roland Barthes Semiotic Analysis - Fikri Afdillah Daulay; Muhammad Habibi Siregar (Jurnal Ilmu Sosial dan Humaniora, 2026)
lyrics of “33X” by Perunggu through Roland Barthes’ semiotic approach. This study is grounded in the emergence of popular music as a medium of symbolic communication that not only provides entertainment but also contains spiritual reflection through poetic language and the life experiences of young people. This study employs a descriptive qualitative method, with data collected through documentation and literature study. The primary data consist of the lyrics of “33X”, while the secondary data are obtained from books, scholarly articles, and literature relevant to semiotics, religiosity, and popular music. Data analysis is conducted through Roland Barthes’ three levels of meaning, namely denotation, connotation, and myth. The findings show that the lyrics of “33X” represent religious values such as monotheism, remembrance of God, surrender to God, patience, self-reflection, positive thinking toward God, intention, and effort. At the denotative level, the lyrics depict human experiences in facing pressure, exhaustion, loss, and the search for life direction. At the connotative level, the lyrics present an invitation to surrender, remember God, accept circumstances, and build spiritual awareness. At the mythical level, this song represents the religiosity of modern Muslim youth who strive to maintain Islamic values amid popular culture. These findings affirm that popular music can serve as a medium of religious communication that conveys spiritual messages implicitly, reflectively, and contextually.